Unraveling the power of sense of coherence: a key predictor of symptom severity among depressive disorders clients - Samah Mohamed Taha; Mona Metwally El-Sayed; Mahmoud Abdelwahab Khedr; Ayman Mohamed El-Ashry; Azza Ibrahim Abdelraof; Hassan Mohammed Sonbol; Manal Mohammed Hawash; Eman Sameh Abd Elhay (BMC Nursing, 2025)
Abstract Background Despite advancements in therapies, the severity of depressive symptoms continues to challenge psychiatric nurses. However, research has indicated that a higher sense of coherence (SOC) can act as a protective factor against the development of diseases and promote faster recovery. Aim This study aimed to investigate whether SOC could serve as an indicator of depressive symptom severity among clients with depression. Design The study employed a cross-sectional design and followed the STROBE checklist for reporting observational studies. Methods A convenient sample of 169 clients with depression participated in the study. The researchers utilized the Antonovsky Sense of Coherence Scale-29 and the Beck Depression Inventory-II to assess SOC and depressive symptoms, respectively. Results The study findings indicated that a substantial proportion of the participants (35.5%) had low Sense of Coherence (SOC) levels, associated with higher depressive symptoms. The severity of depression showed a significant negative correlation with difficulties in understanding and finding meaning in life and challenges in effectively coping with life’s demands (r = -0.626, p < 0.001). The regression analysis revealed that for every one-unit increase in SOC, there was a corresponding decrease of 0.5 units in depressive symptoms. The SOC variable accounted for 39.1% of the variance in depressive symptoms severity. Conclusion Psychiatric nurses should consider implementing interventions to enhance SOC, such as Life Skills Training (LST), psychoeducation, cognitive-behavioral therapy, and mindfulness practices, particularly for depressive disorder clients with a poor sense of coherence.